Infrared characterisation of fossils down to the nanoscale: Insights from an insect in amber - Antoine Vite; Mathieu Thoury; Pierre Gueriau; Jérémie Mathurin; Alexandre Dazzi (Organic Geochemistry, 2026)

Data-driven modelling of volatile solids reduction in municipal sludge anaerobic digesters: Learning from six full-scale plants - Antoine Picard; Danielle Trap; Damien Batstone; Roman Moscoviz; Mathieu Haddad (Bioresource Technology Reports, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Experimental protocols and models for assessing the permeation of antineoplastic drugs through gloves: From a scoping review to a guidelines proposition for future studies - Guillaume Swierczynski; Joris Guyon; Mathieu Molimard; Alain Garrigou; Isabelle Baldi; Catherine Verdun-Esquer; Antoine Villa; Mireille Canal-Raffin (Journal of Hazardous Materials, 2025)

Enhancement of Agroecosystem Multifunctionality by Agroforestry: A Global Quantitative Summary - Antoine Mathieu; Marc‐Olivier Martin‐Guay; David Rivest (Global Change Biology, 2025)
In comparison with conventional agriculture, agroforestry systems improve the delivery of multiple ecosystem services and support greater biodiversity. Yet, the effects of agroforestry on various ecosystem services and biodiversity vary worldwide between climatic regions and system types, and studies often focus on measuring a small number of services or biodiversity indicators. We conducted a quantitative summary of multiple large‐scale meta‐analyses comparing service delivery or biodiversity between agroforestry systems and conventional agricultural systems to capture the global effect of agroforestry on agroecosystem multifunctionality. Data were aggregated from 20 meta‐analyses, many of them global, and response ratios were calculated to assess relative effects of agroforestry systems worldwide on multiple categories of biodiversity indicators and production, regulation, and support services. By combining different datasets that addressed specific ecosystem services or biodiversity indicators and analyzing 3075 comparisons between agroforestry systems and their conventional counterparts, we found that agroforestry enhanced ecosystem service delivery and biodiversity globally by an average of 23%. The effects were more pronounced on supporting and regulating services and biodiversity than on production services. The vast majority of analyzed services and biodiversity indicators were enhanced in agroforestry systems, while few were either not affected or affected negatively. Among ecosystem services analyzed along an aridity gradient, only soil organic carbon (SOC) stocks and forage production varied significantly. The positive effects of agroforestry on SOC stocks were stronger in drier conditions, while those on forage production followed a quadratic trend, with maximal benefits in arid conditions. Our results suggest that broad‐scale adoption of agroforestry in conventional agriculture could benefit agroecosystem multifunctionality globally without sacrificing productivity and would help support sustainable food production.

From planning to implementation: a multi-stakeholder partnership for managing plant invasions in tropical island ecosystems - Mathieu Rouget; Pauline Fenouillas; Emilie Cazal; Margot Caubit; Cédric Ajaguin Soleyen; Eve Balard; Antoine Becker-Scarpitta; Laurent Calichiama; Gael Karczewski; Christophe Lavergne; Benoît Lequette; Roxane L’Horset; et al. (Biological Invasions, 2024)

Reconstruction and verification of mechanism and triggering conditions of the Hermitage landslide at the Vaches Noires cliffs (Normandy) - Mohamed Kouah; Yannick Thiery; Olivier Maquaire; François Nicot; Antoine Wautier; Thomas Roulland; Guillaume Thirard; Mathieu Fressard; Stéphane Costa; Robert Davidson (Geomorphology, 2024)

Drivers of tree establishment in planted windbreaks and riparian buffers: A case study of farms in southern Quebec, Canada - Antoine Mathieu; Alain Cogliastro; David Rivest (Geoderma Regional, 2024)

Tectono-sedimentary evolution of the Suriname margin in the cretaceous: A sequence-stratigraphic framework - V. Delhaye-Prat; Julien Bourget; Gwladys Gaillot; Jérémie Gaillot; François Sapin; Charlotte Fillon; Jing Ye; Tim Wright; Anne-Claire Chaboureau; Nicoletta Buratti; Benoit Magnier; Andrei Belopolsky; et al. (Earth-Science Reviews, 2024)

Fava bean (Vicia faba L.) protein concentrate added to beef burgers improves the bioaccessibility of some free essential amino acids after in vitro oral and gastrointestinal digestion - Susana Ribes; Laurent Aubry; Magdalena Kristiawan; Imen Jebalia; Didier Dupont; Mathieu Guillevic; Antoine Germain; Guillaume Chesneau; Thierry Sayd; Pau Talens; Marie-Agnès Peyron; Véronique Santé-Lhoutellier (Food Research International, 2024)

HBM4EU chromates study – PFAS exposure in electroplaters and bystanders - Thomas Göen; Annalisa Abballe; Radia Bousoumah; Lode Godderis; Ivo Iavicoli; Anna Maria Ingelido; Veruscka Leso; Johannes Müller; Sophie Ndaw; Simo P. Porras; Jelle Verdonck; Tiina Santonen; et al. (Chemosphere, 2024)

Pulmonary Histoplasmosis in People Living with Human Immunodeficiency Virus in French Guiana: Clinical Epidemiology, Medical Imaging and Prognostic - Morgane Bourne-Watrin; Antoine Adenis; Gary Doppelt; Magaly Zappa; Loïc Epelboin; Mathieu Nacher; Jeanne Bigot; Kinan Drak Alsibai; Romain Blaizot; Denis Blanchet; Magalie Demar; Geneviève Guillot; et al. (Mycopathologia, 2023)
Background Histoplasmosis is mainly described as a disseminated disease in people living with HIV (PLHIV). Compared to historical descriptions in immunocompetent individuals, knowledge is lacking on the detailed clinical and radiological findings and outcomes of pulmonary histoplasmosis (PH). Overlooked or misdiagnosed with other AIDS-defining condition, prognostic of PLHIV may be at risk because of inappropriate care. Methods A retrospective multicentric study was conducted in PLHIV from French Guiana between January 1988 and October 2019. Proven PH were documented through mycological direct examination, culture, or histology. Patients with concomitant respiratory infections were excluded. Results Among 65 patients, sex ratio M:F was 2.4 with a median age of 39 years [IQR 25–75%: 34–44]. Median CD4 count was 24 cells/mm 3 [11–71], with histoplasmosis as the AIDS-defining condition in 88% and concomitant AIDS-defining conditions in 29%. Clinical findings were fever (89%), cough (58%), dyspnea (35%), expectoration (14%), and hemoptysis (5%). Sixty-one X-rays and 24 CT-scans were performed. On X-rays, an interstitial lung disease was mainly found (77%). On CT-scans, a nodular pattern was predominant (83%): mostly miliary disease (63%), but also excavated nodules (35%). Consolidations were present in 46%, associated with miliary disease in 21%. Thoracic lymphadenopathies were found in 58%, mainly hilar and symmetric (33%). Despite antifungal treatment, case-fatality rate at one month was 22%. Conclusion When faced with an interstitial lung disease on X-rays or a miliary pattern on CT-scans in advanced PLHIV, physicians in endemic areas, apart from tuberculosis or pneumocystosis, should include histoplasmosis as part of their differential diagnoses.

The DeepFaune initiative: a collaborative effort towards the automatic identification of European fauna in camera trap images - Noa Rigoudy; Gaspard Dussert; Abdelbaki Benyoub; Aurélien Besnard; Carole Birck; Jérome Boyer; Yoann Bollet; Yoann Bunz; Gérard Caussimont; Elias Chetouane; Jules Chiffard Carriburu; Pierre Cornette; et al. (European Journal of Wildlife Research, 2023)

Snow cover persistence as a useful predictor of alpine plant distributions - Thomas Panchard; Olivier Broennimann; Mathieu Gravey; Grégoire Mariethoz; Antoine Guisan (Journal of Biogeography, 2023)
Aim Snow cover persistence (SCP) has significant effects on plants in high‐elevation ecosystems. It determines the length of the growing season, provides insulation against low temperatures and influences water availability, thereby shaping the vegetation mosaic. Despite its importance, SCP is rarely used in plant species distribution modelling. In this study, we examine whether incorporating SCP in plant species distribution models (SDMs) improves their predictive power. We investigate the link between species' ecology and SDM improvements by the addition of various SCP predictors. Location Western Swiss Alps. Taxon 206 alpine flowering plants (angiosperms). Methods We produced three maps of landsat satellite‐based SCP indices over an entire mountain region, one of them using an online open access platform allowing quick and easy replication and used them as a predictor in plant SDMs alongside commonly used predictors. We tested whether this improved the predictive performance of plant SDMs. Results All three SCP indices improved the overall SDM predictive accuracy, but the overall improvement was potentially limited by their correlation with other climatic predictors. Alpine plant species known for their dependence on snow benefited more from the additional snow information. Main Conclusions SCP should be used for predicting at least the distribution of alpine, snow‐related plant species. Given that adding snow cover improves SDMs and that snow duration decreases as climate warms, future predictions of alpine plant distributions should account for both snow predictor and associated snow change scenarios.

Are historical stage records useful to decrease the uncertainty of flood frequency analysis ? A 200-year long case study - Mathieu Lucas; Benjamin Renard; Jérôme Le Coz; Michel Lang; Antoine Bard; Gilles Pierrefeu (Journal of Hydrology, 2023)

Factors associated with internal contamination of nurses by antineoplastic drugs based on biomonitoring data from a previous study - Antoine Villa; Arna Geshkovska; Gauthier Bellagamba; Isabelle Baldi; Mathieu Molimard; Catherine Verdun-Esquer; Marie-Pascale Lehucher-Michel; Mireille Canal-Raffin (International Journal of Hygiene and Environmental Health, 2023)

Wizard: Unsupervised goats tracking algorithm - Jehan-Antoine Vayssade; Xavier Godard; Mathieu Bonneau (Computers and Electronics in Agriculture, 2023)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

How public policies and other events can shape spatial distribution of local activities over time? An investigation based on spatial micro-data - Jean Dubé; Ousmane Dieng; Mathieu Lévesque; Antoine Racine; Olivier Roberge; Thibault Trapé (Land Use Policy, 2023)

Telomeres, the loop tying cancer to organismal life‐histories - Beata Ujvari; Nynke Raven; Thomas Madsen; Marcel Klaassen; Antoine M. Dujon; Aaron G. Schultz; Leonard Nunney; Jean‐François Lemaître; Mathieu Giraudeau; Frédéric Thomas (Molecular Ecology, 2022)
Recent developments in telomere and cancer evolutionary ecology demonstrate a very complex relationship between the need of tissue repair and controlling the emergence of abnormally proliferating cells. The trade‐off is balanced by natural and sexual selection and mediated via both intrinsic and environmental factors. Here, we explore the effects of telomere‐cancer dynamics on life history traits and strategies as well as on the cumulative effects of genetic and environmental factors. We show that telomere‐cancer dynamics constitute an incredibly complex and multifaceted process. From research to date, it appears that the relationship between telomere length and cancer risk is likely nonlinear with good evidence that both (too) long and (too) short telomeres can be associated with increased cancer risk. The ability and propensity of organisms to respond to the interplay of telomere dynamics and oncogenic processes, depends on the combination of its tissue environments, life history strategies, environmental challenges (i.e., extreme climatic conditions), pressure by predators and pollution, as well as its evolutionary history. Consequently, precise interpretation of telomere‐cancer dynamics requires integrative and multidisciplinary approaches. Finally, incorporating information on telomere dynamics and the expression of tumour suppressor genes and oncogenes could potentially provide the synergistic overview that could lay the foundations to study telomere‐cancer dynamics at ecosystem levels.

Chemerin regulates normal angiogenesis and hypoxia-driven neovascularization - Cyrine Ben Dhaou; Kamel Mandi; Mickaël Frye; Angela Acheampong; Ayoub Radi; Benjamin De Becker; Mathieu Antoine; Nicolas Baeyens; Valérie Wittamer; Marc Parmentier (Angiogenesis, 2022)
Chemerin is a multifunctional protein initially characterized in our laboratory as a chemoattractant factor for leukocyte populations. Its main functional receptor is CMKLR1. We identified previously chemerin as an anti-tumoral factor inhibiting the vascularization of tumor grafts. We show here that overexpression of bioactive chemerin in mice results in a reduction of the density of the retinal vascular network during its development and in adults. Chemerin did not affect vascular sprouting during the post-natal development of the network, but rather promoted endothelial cell apoptosis and vessel pruning. This phenotype was reversed to normal in CMKLR1-deficient mice, demonstrating the role of this receptor. Chemerin inhibited also neoangiogenesis in a model of pathological proliferative retinopathy, and in response to hind-limb ischemia. Mechanistically, PTEN and FOXO1 antagonists could almost completely restore the density of the retinal vasculature, suggesting the involvement of the PI3-kinase/AKT pathway in the chemerin-induced vessel regression process.

Nurses’ internal contamination by antineoplastic drugs in hospital centers: a cross-sectional descriptive study - Antoine Villa; Mathieu Molimard; Dunia Sakr; Régis Lassalle; Emmanuelle Bignon; Béatrice Martinez; Magali Rouyer; Simone Mathoulin-Pelissier; Isabelle Baldi; Catherine Verdun-Esquer; Mireille Canal-Raffin (International Archives of Occupational and Environmental Health, 2021)

Using a robust multi‐settings inference framework on published datasets still reveals limited support for the abundant centre hypothesis: More testing needed on other datasets - Mathieu Chevalier; Olivier Broennimann; Antoine Guisan (Global Ecology and Biogeography, 2021)
Aim The abundant centre hypothesis (ACH) predicts a negative relationship between species abundance and the distance to the geographical range centre. Since its formulation, empirical tests of the ACH have involved different settings (e.g. the distance to the ecological niche or to the geographical range centre), but studies found contrasting support for this hypothesis. Here, we evaluate whether these discrepancies might stem from differences regarding the context in which the ACH is tested (geographical or environmental), how distances are measured, how species envelopes are delineated, how the relationship is evaluated and which data are used. Location The Americas. Time period 1800–2017. Major taxa studied Mammals, birds, fish, and tree seedlings. Methods Using published abundance data for 801 species, together with species range maps, we tested the ACH using three distance metrics in both environmental and geographical spaces with range and niche envelopes delineated using two different algorithms, totalling 12 different settings. We then evaluated the distance–abundance relationship using correlation coefficients (traditional approach) and mixed‐effect models to reduce the effect of sampling noise on parameter estimates. Results Similar to previous studies, correlation coefficients indicated an absence of effect of distance on abundance for all taxonomic groups and settings. In contrast, mixed‐effect models highlighted relationships of various strengths and shapes, with a tendency for more theoretically supported settings to provide stronger support for the ACH. The relationships were however not consistent across taxonomic groups and settings, and were sometimes even opposite to ACH expectations. Main conclusions We found mixed and inconclusive results regarding the ACH. These results corroborate recent findings, and suggest either that our ability to predict abundances from the location of populations within geographical or environmental spaces is low, or that the data used here have a poor signal‐to‐noise‐ratio. The latter calls for further testing on other datasets using the same range of settings and methodological framework.

The ID NOW COVID-19, a high-speed high-performance assay - Eric Farfour; M. Asso-Bonnet; M. Vasse; Emilie Catherinot; Colas Tcherakian; Antoine Magnan; Simon Chauveau; Sylvie Colin de Verdière; Hélène Salvatore; Antoine Roux; Benjamin Zuber; Charles Cerf; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

COVID-19 or not COVID-19? Compared characteristics of patients hospitalized for suspected COVID-19 - Thomas Rogier; Isabelle Eberl; Florian Moretto; Thibault Sixt; François-Xavier Catherine; Clémentine Estève; Maroua Abdallahoui; Lucile Behague; Antoine Coussement; Lucas Mathey; Sophie Mahy; Marielle Buisson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Correction to: Using Causal Inference in Field Development Optimization: Application to Unconventional Plays - Antoine Bertoncello; Georges Oppenheim; Philippe Cordier; Sébastien Gourvénec; Jean-Philippe Mathieu; Eric Chaput; Tobias Kurth (Mathematical Geosciences, 2020)

Using Causal Inference in Field Development Optimization: Application to Unconventional Plays - Antoine Bertoncello; Georges Oppenheim; Philippe Cordier; Sébastien Gourvénec; Jean-Philippe Mathieu; Eric Chaput; Tobias Kurth (Mathematical Geosciences, 2020)
In the current era of big data and machine learning, a strong focus exists on prediction and classification. In industrial applications, however, many important questions are not about prediction or classification; rather, they are causal: if I change A, what will happen to B? Traditional regression techniques such as machine learning optimize predictions based on correlations seen in the data and are not robust tools for epidemiologists and biostatisticians when evaluating the efficacy of new treatments or medications using observational data. Therefore, a set of statistical tools have been developed to go beyond correlations and aim to make inferences about causal relationships between variables. The goal of the present work is to apply one of these statistical tools, propensity score matching, in the oil and gas context, which is a novel application of the method. Two case studies are presented, one on proppant type and the other on lateral length, to determine their respective impacts on productivity.

Detecting stratigraphical issues using direct radiocarbon dating from small‐mammal remains - Juan Rofes; Sophie Cersoy; Antoine Zazzo; Aurelien Royer; Pierre‐Yves Nicod; Veronique Laroulandie; Mathieu Langlais; Yvan Pailler; Celine Leandri; Franck Leandri; Matthieu Lebon; Anne Tresset (Journal of Quaternary Science, 2020)
Frequently preserved in archaeological and palaeontological sites, the tiny size of small‐mammal remains favours percolations into underlying layers along stratigraphic sequences. This is one of the various post‐depositional processes that may affect the integrity of the original deposits and therefore the subsequent scientific interpretations. Recent developments in sample preparation offer the possibility of detecting intrusive episodes through the absolute dating of minute amounts of bone (down to 10 mg), meaning that isolated elements (such as mandibles in this case) are sufficient to obtain reliable radiocarbon dates if collagen is moderately to well preserved. The radiocarbon dates obtained here for small‐mammal bones (recovered from pre‐Bølling to recent deposits) and their comparison with previous dates obtained from other sources (large‐mammal bones, charcoal, botanical samples, etc.), with different protocols and instruments, illustrate the potential of small‐mammal dating to reveal (and eventually contribute a solution to) stratigraphical issues in different archaeological contexts.

Virus preparations from the mixed-infected P70 Pinot Noir accession exhibit GLRaV-1/GVA ‘end-to-end’ particles - Antoine Alliaume; Catherine Reinbold; Mathieu Erhardt; Monique Beuve; Jean-Michel Hily; Olivier Lemaire; Etienne Herrbach (Archives of Virology, 2018)

Natural hazards in Goma and the surrounding villages, East African Rift System - Charles M. Balagizi; Antoine Kies; Marcellin M. Kasereka; Dario Tedesco; Mathieu M. Yalire; Wendy A. McCausland (Natural Hazards, 2018)

Sediment characteristics and microbial mats in a marine mangrove, Manche-à-eau lagoon (Guadeloupe) - Swanne Gontharet; Antoine Crémière; Marie-Madeleine Blanc-Valleron; Mathieu Sebilo; Olivier Gros; Anniet M. Laverman; David Dessailly (Journal of Soils and Sediments, 2017)

Phenological response of a key ecosystem function to biological invasion - Maria Alp; Julien Cucherousset; Mathieu Buoro; Antoine Lecerf (Ecology Letters, 2016)
Although climate warming has been widely demonstrated to induce shifts in the timing of many biological events, the phenological consequences of other prominent global change drivers remain largely unknown. Here, we investigated the effects of biological invasions on the seasonality of leaf litter decomposition, a crucial freshwater ecosystem function. Decomposition rates were quantified in 18 temperate shallow lakes distributed along a gradient of crayfish invasion and a temperature‐based model was constructed to predict yearly patterns of decomposition. We found that, through direct detritus consumption, omnivorous invasive crayfish accelerated decomposition rates up to fivefold in spring, enhancing temperature dependence of the process and shortening the period of major detritus availability in the ecosystem by up to 39 days (95% CI : 15–61). The fact that our estimates are an order of magnitude higher than any previously reported climate‐driven phenological shifts indicates that some powerful drivers of phenological change have been largely overlooked.

Potential of Opuntia ficus-indica for air pollution biomonitoring: a lead isotopic study - Eliane El Hayek; Antoine El Samrani; Bruno Lartiges; Veronique Kazpard; Mathieu Benoit; Marguerite Munoz (Environmental Science and Pollution Research, 2015)

Pharmacokinetic/Pharmacodynamic Modeling of Renin-Angiotensin Aldosterone Biomarkers Following Angiotensin-Converting Enzyme (ACE) Inhibition Therapy with Benazepril in Dogs - Jonathan P. Mochel; Martin Fink; Mathieu Peyrou; Antoine Soubret; Jérôme M. Giraudel; Meindert Danhof (Pharmaceutical Research, 2015)

Alcohol cues increase cognitive impulsivity in individuals with alcoholism - Xavier Noël; Martial Van der Linden; Mathieu d’Acremont; Antoine Bechara; Bernard Dan; Catherine Hanak; Paul Verbanck (Psychopharmacology, 2007)